The new way of working in the post-covid-19 scenario in the beverage industry. what has changed? - Lima, Mayra Braga da Silva; Cunha, Luana Maria Meireles; Lima, Consuelo Lucia Sousa de (Brazilian Journal of Production Engineering, 2022)
The COVID-19 pandemic spread suddenly throughout the world, changing the reality of an entire society, which had to adapt to this new scenario. The food industries were affected, and to keep their functioning a lot, they needed to look for ways to remain active, providing an even safer working environment for their employees. The study aimed to show how changes occurred in a beverage industry during the COVID-19 pandemic. For this, a data survey was carried out in the industry in question, with an application of a checklist based on the General Health Protocol of Decree No. 800, of May 31, 2020, by the factory sectors, in addition to a questionnaire for employees, to highlight the changes that have taken place in the company's day-to-day activities. After this survey, changes and conduct were identified, such as social distancing, and also the implementation of the Daily Safety Dialogues (DDS) with themes related to prevention against COVID-19. After applying the checklist, it was verified that the industry in question managed to achieve about 94% of compliance with Decree No. 800, of May 31, 2020. Therefore, the installation of these prevention measures and the results obtained through the checklist evidenced that the beverage industry provides a safe environment for its employees in the context of the COVID-19 pandemic.
Keywords: COVID-19; Pandemic; Beverage Industry; Security